Nilai-Nilai Estetika Melayu dalam Lirik Lagu Karya Rhoma Irama Kajian terhadap Lirik Lagu “Seni” dan “Buta Tuli” - Moh. Muzakka (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
The purpose of this research is to reveal the aesthetic values in the lyrics of the song by Rhoma Irama, especially in the lyrics of the song "Seni" and "Buta Tuli". Aesthetic theory used to study both the lyrics are Malay aesthetic theory formulated by Braginsky. It summed up the three spheres functions in Malay literature consists are a function of beauty (indah), pragmatic function (faidah), and spiritual function (kamal). The results of the analysis show that the two lyrics of the Rhoma Irama song are very loaded with these three elements of functions. Both Rhoma Irama song lyrics are arranged in beautiful words and reveal pragmatic values. Both values are raised to achieve the highest value, which is service to the Creator (God).